Development of Genre-Based Arabic Teaching Materials Inspired by Kediri Ulama to Enhance Students’ Motivation - Zubairi, Ahmad; Asrori, Imam; Nurhidayati; Judijanto, Loso; Darmanto; Azizah, Suti Mega Nur (IAIN Madura, 2025)
An ongoing issue in the majority of schools is the lack of enthusiasm among students for Arabic classes. The purpose of this research is to identify effective strategies for piquing students' interest in Arabic language acquisition through the creation of genre-based pedagogical resources informed by the works of Kediri ulama. There are 60 Students from Madrasah Aliyah Sunan Gunung Jati who were divided into two groups for the study: one group was given a pre-test and the other group was given an experimental assignment. The study used a quasi-experimental approach. Product Moment Correlation, Cronbach's Alpha, Levene's test, Shapiro-Wilk test, and Independent Sample T-test were used to assess the quantitative data that was collected from a learning motivation questionnaire. Students' intrinsic motivation to learn Arabic was significantly higher in the experimental group compared to the control group after the development and implementation of genre-based instructional materials. To ensure that instructional materials are relevant and practical in madrasah education, the study stresses the importance of collaboration among historians, educators, and professionals in the Arabic language.